2018
DOI: 10.3389/fmars.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of the rbcL and psaA Genes From Single Cells Demonstrate a Rhodophyte Origin of the Prey in the Toxic Benthic Dinoflagellate Ostreopsis

Abstract: Phagotrophy of the harmful benthic dinoflagellates of the genus Ostreopsis has long been inferred based on observations of food particles present inside cells, but the prey has not yet been identified. This study aimed to investigate the seasonal dynamics of benthic dinoflagellates Ostreopsis spp. in temperate Korean coastal sites, with special emphasis on their phagotrophy. Further, prey species were identified by extracting the ingested food particles from single Ostreopsis cells and determining their rbcL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Ostreopsis species around Jeju Island has been reported since 2010 [44,50]. Moreover, Hwang et al [13,51] reported the novel cytotoxic non-PLTX compounds Ostreol A and B in the strain isolated from Jeju Island, which have not both been reported in any other strain.…”
Section: Discussionmentioning
confidence: 99%
“…Ostreopsis species around Jeju Island has been reported since 2010 [44,50]. Moreover, Hwang et al [13,51] reported the novel cytotoxic non-PLTX compounds Ostreol A and B in the strain isolated from Jeju Island, which have not both been reported in any other strain.…”
Section: Discussionmentioning
confidence: 99%
“…ovata were also found on the turf dominated community i.e., in a complex intricate matrix of small Corallinales, Ceramiales (both Florideophyceae) and other filamentous algae (Meroni et al, 2018) as reported in Vila et al (2001) for Ellisolandia elongata and in Blanfuné et al (2015) for Jania rubens. Lee and Park (2018) also showed that Ostreopsis sp. ingested rhodophytes because of their soft cell membrane containing microfibrillar and sulfated galactans (see section 4.2).…”
Section: Macroalgaementioning
confidence: 96%
“…Almada et al (2017) showed evidence of phagotrophy using LysoSensor staining even if the prey inside the cells were not discernable. More recently, using molecular approaches, Lee and Park (2018) defined the red bodies as digestive vacuoles containing ingested red macroalgae (Class Florideophyceae).…”
Section: Importance Of the Mucus In Ostreopsis Biological Interactionsmentioning
confidence: 99%
“…2). Under these circumstances, it is critical to determine whether these dinoflagellates can survive and overwinter in the South and Baek (2012aBaek ( , 2012b, Shah et al (2013aShah et al ( , 2013bShah et al ( , 2014a, and Lee and Park (2018).…”
Section: Geographical Distribution Of Benthic Dinoflagellates In Korean Watersmentioning
confidence: 99%